"Computational Analysis of the Effect of fbn1 Gene Mutations in the Marfan Syndrome" - H Mohabatkar (Iranian Journal of Public Health, 2004)
Fibrillin is a large glycoprotein synthesized in the tissues involved in Marfan syndrome, and known to be involved in tissue elasticity. The syndrome is corresponded to fbn1 gene and is characterized by cardiovascular, ocular, and skeletal abnormalities. N-terminus of fibrillin 1 binds to microfibril-associated glycoprotein 1 (MAGP-1) in a calcium-dependent manner. In this study, the amino acid sequence of fibrillin protein of a patient with Marfan syndrome (accession No. XM- 034890) has been compared to the amino acid sequence of normal fibrillin (accession No. P-35555). In this patient, mutations causing a Gly (267) to Thr and Tyr (532) to Cys amino acids changes have been occurred. Method of Garnier was used to predict the secondary structure of the proteins and probable N-glycosylation sites were searched. Results of these analyses show no significant structural difference between the mutant and normal fibrillin proteins. Although in some cases characterization of the binding requirements has shown that a folded, secondary structure of fibrillin was necessary for binding, our results are in agreement with those findings that at least in some cases, fibrillin gene defects are not sole determinants of Marfan phenotype.